Destabilizing effects of terrorism on party system stability - Hunter, Lance Y. (Terrorism and political violence, 2018)
In democracies with stable party systems, voters can more easily trace policy decisions from parties and representatives within the government to specific policy outcomes. Consequently, party system stability (PSS) has been reportedly linked to a variety of factors including economic conditions, democratic performance, political institutions, and socioeconomic cleavages. While informative, these lessons offer precious little insight into other factors that can destabilize a party system. In this work, we surmise that terrorist attacks have important implications for two commonly used measures of PSS. The results of a pooled, cross-sectional time series analysis confirm our hypothesis: deadly attacks proximate to elections destabilize party systems, even when controlling for multiple standard controls. In addition, the level of democratic consolidation within states also influences the degree that fatal terrorist attacks affect party system stability. These findings are based on terrorism data collected from the Global Terrorism Database and from PSS data compiled by the authors.